GOUT WITH TOPHUS MIMICKING A TUMOR OF THE THORACIC SPINE - V. N. Sorotskaya; M. S. Eliseev (Научно-практическая ревматология, 2018)
The paper describes a rare case of thoracic spine involvement in a 28-year-old patient with gout that was manifested by acute neurologic symptoms (lower extremity paresis with pelvic organ dysfunction) and that required emergency surgery. Similar cases that are previously described, including the possible variants of the clinical manifestations, tophus localization, surgical treatment, risk factors for axial tophus formation, are separately discussed.